SCHOOL STUDENTS’ MOTIVATION FOR LEARNING PHYSICS: HOW DOES INSTRUCTIONAL CLARITY IN PHYSICS LESSONS ENGAGE? - Peciuliauskiene, Palmira (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
The article deals with the eighth-grade school students’ motivation for learning physics. The spectrum of factors influencing the school students’ motivation for learning physics is very wide. This study addresses the phenomenon of school students’ motivation for learning physics in the light of an educational factor. We analyze the role of instructional clarity in physics lessons on school students’ motivation for learning physics based on TIMSS 2019 data set of Lithuania and Finland. To disclose the influence of instructional clarity in physics lessons on school students’ motivation for learning physics confirmatory factor analysis (CFA) and structural equation modelling (SEM) was used. The results of our research reveal that instructional clarity in physics lessons is directly and positively associated with school students’ motivation for learning physics. SEM results disclosed not only significance but magnitudes of associations between instructional clarity in physics lessons and school students’ motivation for learning physics as well.